Potensi Pengembangan Ekonomi Pariwisata di Desa Biting Kabupaten Ponorogo - Muhammad Chifdhia Salas; Faruq Ahmad Futaqi (Journal of Economics, Law, and Humanities, 2024)
This field study uses data collection techniques, such as observation, documentation, and interviews, to explore and analyze the potential for tourism economic development in Biting Village, Ponorogo Regency. The data analysis technique used in this research is data reduction data presentation. The results of the research show that the tourism economic potential in Biting Village, Ponorogo Regency, with the best tourist attractions, are Plered Paragliding Hill and Suharto Hill, Camping Hill, Sumorobangun Flower Park, Setono Pangonan Cultural Site, Sumorobangun River, Biting Rainbow Bridge, Biting Rest Area, the art of Ponorogo reyog and karawitan. Development and construction of tourism infrastructure include attractions, accessibility, amenities, human resources, community involvement, industry, and marketing or promotion. The development of tourism economic potential in Biting Village, Ponorogo Regency, has had a positive impact, including increasing the level of life of the community, culture, and traditions being sustainable, providing economic benefits for the community, growth of small and medium industries, promoting of local products, preservation of nature and the environment, improving the image nation, fostering a sense of love for the homeland, strengthening national identity and unity, and strengthening friendship between nations.